Pearls and pitfalls in pediatric imaging variants and other difficult diagnoses - Daldrup-Link, Heike E.; Newman, Beverley (Cambridge University Press, 2014)
This collection of over 90 highly illustrated case studies explores major and confusing problems in pediatric imaging. All relevant imaging modalities are covered, including ultrasound, conventional radiography, fluoroscopy, CT, MR, nuclear and molecular imaging, and interventional radiology. The authors present a strategy for recognizing key information in order to reach an accurate diagnosis, and each case includes differential diagnoses and key teaching points, alerting the reader to common pitfalls in the interpretation of pediatric radiological images. This is a highly valuable resource for trainee pediatric radiologists, and general radiologists who encounter pediatric patients. It will particularly help people preparing for exams, including the core exam, the certifying exam or CAQ exams, as well as pediatric radiologists who want to refresh their knowledge on particular topics. It will also be of interest to pediatricians who wish to improve their diagnostic proficiency and understanding of imaging studies.